Comparison of Meconium Microbiome in Dizygotic and Monozygotic Twins Born by Caesarean Section (CS) - Yang, Jing; Yao, Su; Cheng, Kun; Xu, Lili; Hou, Lingling; Wei, Yuan; Feng, Huijun; Yu, Xuejian; Zhang, Xin; Tong, Xiaomei; Li, Zailing; Zhao, Yangyu (Frontiers in Microbiology, 2020)
The early-life microbiota triggers life-long effects on physiological functions and health disorders. Previous studies in adult twins or animal models have revealed associations between host genetics and the harmonious microbiota. However, such associations may be obscured by the fact that each intra-pair of twins will continually encounter various environmental factors as they grow up. Here, we collected the meconium samples from nineteen dizygotic pairs (DZ, n=38) and nine monozygotic pairs (MZ, n=18) with cesarean delivery, and 16S rRNA gene sequencing was performed to profile the microbiome at birth. Diversity analysis showed that alpha diversity was not significantly different between two groups, whereas beta diversity of MZ twins was significantly lower than that of either DZ twins or unrelated individuals (p < 0.05). Two groups had very similar microbial classifications, but certain taxa differed in their relative abundances. MZ individuals showed a higher Proteobacteria to Firmicutes ratio, and the relative abundances of five genera including Rheinheimera and Megamonas were significantly higher compared to that of DZ individuals. Co-occurrence analysis in each group showed more complicated microbial interactions in DZ than MZ twins, although 22 shared bacterial genera co-existed in two groups, with both Rheinheimera and Megamonas having different centralities in their respective co-occurrence networks. Mean intra-class correlation coefficient (ICC) were also significantly higher for MZ (0.312) compared to DZ twins (0.138) (p < 0.05).The predicted microbial gene functions related to carbohydrate were higher in DZ group, whereas folding, sorting, degradation, cell motility pathways and energy metabolism were markedly over-represented in the microbiota of MZ group. In summary, our study uncovered that microbial diversity and components of the meconium microbiome between DZ and MZ twins were partially consistent with that in singleton neonates by cesarean delivery, but several distinctions related to the heritability supported genetic contributions to intestinal microbiome in early life.